Stroke Lateralization in Large Hemisphere Infarctions: Characteristics, Stroke-Related Complications, and Outcomes - Li, Jie; Zhang, Ping; Liu, Yingying; Chen, Wanli; Yi, Xingyang; Wang, Chun (Frontiers in Neurology, 2021)
Objectives: To assess the hemispheric differences in characteristics, stroke-related complications and outcomes of patients with large hemisphere infarctions (LHI). Methods: We enrolled consecutive patients admitted with 24 hours with the diagnosis of LHI (defined as an ischemic stroke involving more than 50% of the territory of the middle cerebral artery in computed tomography and/or magnetic resonance imaging). Univariate and multivariate analysis was performed to explore the association between lateralization and stroke-related complications and clinical outcomes. Results: 314 LHI patients were enrolled, with 171 (54.5%) right hemispheric involvement. Right-sided LHI patients had lower baseline National Institutes of Health Stroke Scale (NIHSS) score (18 vs. 22, p﹤0.001), higher frequency of atrial fibrillation (69.0% vs. 52.4%, p=0.003) and higher proportion of cardio-embolism (73.1% vs. 56.6%, p=0.013) than the left. Right-sided LHI had higher incidence rates of malignant brain edema (MBE) (48.5% vs. 30.8%, p=0.001) and composite of cardiovascular events (29.8 % vs. 17.5%, p=0.011) during hospitalization. The incidence rate of 1-month mortality (34.5% vs. 23.8%, p=0.036) was higher in right-sided LHI patients, but there were no hemispheric differences in the incidence rates of 3-month mortality and unfavorable outcome (both p﹥0.05). Multivariate analyses suggested right hemisphere involvement was independently associated with increased risk of malignant brain edema (adjusted OR 2.37, 95 % CI 1.26 to 4.43, p=0.007) and composite of cardiovascular events (adjusted OR 2.04, 95 % CI 1.12 to 3.72, p=0.020). However, it was not independently associated with 1-month death, 3-month mortality, and 3-month unfavorable outcome (all p﹥0.05). Conclusions: Right-sided LHI patients had higher frequency of atrial fibrillation and cardio-embolism than the left-sided. Right hemisphere involvement was independently associated with increased risk of MBE and composite of cardiovascular events during hospitalization, whereas stroke lateralization was not an independent predictor of mortality and unfavorable outcome in LHI patients.